KUOTA KETERWAKILAN PEREMPUAN DALAM REKRUITMEN PENGURUS DAN CALEG DI DPW PAN JAWA TIMUR PADA PEMILU 2014 - Suwarko, Andi (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This article examines the political representation of women’s quota required for both political party in the structure of the political party and legislative candidates in the 2014 election. The research mainly deals with question on how the implementation and obstacles of the women’s quota for candidates are. Based on qualitative approach, the resultsof the study indicate that; first,the implementation of recruitment of executive board members by DPW PAN of East Java has been done through a closed mechanism, while the recruitment of legislative candidates washeldin an open mechanism. The quota representationis driven more by external motivation, namely regulatory of quota, rather than internal one, i.e. political awareness.Second, the difficulties in fulfilling the quota of women’s representation of Parliament in DPW PAN of East Java have beencaused mainly by high political cost, low-level popularity, limitedness of female candidate’scapacity, and limitedness of social and political networking of the candidates.